Product quality evaluation: Selection among the women buyers in Kelantan - Marzuki, Ibrahim; Mohd Zamani, Daud; Nur Syafinaz, Mohd Anuar (2021)
Kelantan is one of the states that have been focusing on jewellery buyers. The features of Kelantan jewellery can be seen through a unique design, traditional concept and offered at a very reasonable price. Therefore, this study is aimed at identifying the level of knowledge and quality evaluation of jewellery products that are often judged by more than one quality feature. Quantitative methods are used to achieve this goal. The main data were collected through questionnaire survey method by interviewing 210 respondents. Respondents consist of Malay women buyers around gold shop in Kota Bharu city. Data collected and analyzed using a simple percentage method is descriptive statistics (frequency distribution and mean) and translated into table form. The collected data include demographic profiles, knowledge of jewellery and evaluation of jewellery products. The result of this research is used as a scientific reference to the parties involved directly or indirectly in this field. With the information and data obtained it can contribute to further developing the local jewellery industry.